Kulturowe aspekty zarządzania personelem w organizacjach - Kłos, Zbigniew (Cultural Aspect of Personnel Management in Organizations, 2008)
In the paper, different aspects of relation between advancement of organizational culture and the way of personnel management are discussed. First, the definitions of "organizational culture" are presented. Then the main elements in the area of personnel management are outlined. The conditions of behaviour in above-mentioned elements are presented, illustrated with the cases. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 31, s. 314-326